2013
DOI: 10.1007/s10585-013-9626-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts stimulate the osteogenic and metastatic progression of castration-resistant prostate cancer in a novel model for in vitro and in vivo studies

Abstract: Castration-resistant prostate cancer (CRPC) is strongly associated with sclerotic bone metastases and poor prognosis. Models that mimic human CRPC are needed to identify the mechanisms for prostate cancer (PC) growth in bone and to develop new therapeutic strategies. We characterize a new model, LNCaP-19, and investigate the interaction between tumor cells and osteoblasts in the sclerotic tumor response of CRPC. Osteogenic profiling of PC cell lines (LNCaP-19, LNCaP, C4-2B4, and PC-3) was performed by gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Osteoblasts are the cells responsible for the formation and mineralization of new bone. We and others have previously shown that osteoblasts are stimulated by PC tumor cells . In addition, we demonstrated that osteoblasts induce a more aggressive phenotype along with osteomimicry in osteoblastic CRPC cells .…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Osteoblasts are the cells responsible for the formation and mineralization of new bone. We and others have previously shown that osteoblasts are stimulated by PC tumor cells . In addition, we demonstrated that osteoblasts induce a more aggressive phenotype along with osteomimicry in osteoblastic CRPC cells .…”
Section: Introductionsupporting
confidence: 73%
“…We and others have previously shown that osteoblasts are stimulated by PC tumor cells . In addition, we demonstrated that osteoblasts induce a more aggressive phenotype along with osteomimicry in osteoblastic CRPC cells . Together with their role in the pre‐metastatic niche, this makes osteoblasts important players in both establishment and growth of sclerotic bone metastases.…”
Section: Introductionsupporting
confidence: 59%
“…Bone microtumors were established by intratibial (i.t.) injections (right leg tibiae) with PC3-PSCA cells under anesthesia, as previously described [20]. After implantation, the animals received analgesics (Rimadyl; 5 mg/kg) for 5 days.…”
Section: Alpha-rit Of Microtumorsmentioning
confidence: 99%
“…PGC cells are able to synthesize substances with a significant osteostimulatory effect, in particular, prostate specific antigen, endothelin-1, insulin-like growth factor 1 and others. These compounds have a direct effect on the osteogenesis in metastasis foci of PGC and possibly PC development in PGC tissue [8]. Similar substances, other than prostate specific antigen, also have been found in bone tissue [9,10].…”
mentioning
confidence: 66%